Pengaruh Disiplin, Komunikasi, dan Stres Kerja terhadap Kinerja Karyawan PT. Sumatera Speciality Coffees Berastagi - Sindy Sintia; Ide Tria Nita Br Ginting; Andre Fitriano (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The purpose of this study is to assess how work discipline, communication, and work stress affect the work performance of staff at PT. Kopi Khas Sumatera. Workers are an important part of achieving business goals, so it is very important to understand things about staff work results. The success of a company not only depends on strategy or capital but also on how optimal employees perform in their respective roles. Therefore, performance is a critical aspect to monitor and evaluate. Information obtained from distributing questionnaires has been tested for validity and accuracy of information. The validity test shows that all items have a calculated r-value greater than 0.213, indicating that all questionnaire statements are valid. Meanwhile, the information straightness test using the Kolmogorov-Smirnov method shows a normal distribution of information, with a significant number of 0.200 which exceeds the threshold of 0.05. From multiple linear regression analysis, the formula Y = 2.067 + 0.310X₁ + 0.304X₂ + 0.445X₃ is obtained. This model indicates that work discipline (X₁), communication (X₂), and work stress (X₃) all positively influence staff work performance (Y). The F-calculated value of 98.024 is significantly greater than the F-table value of 2.72, and the significance value of 0.000 is less than 0.05. These findings confirm that all three independent variables simultaneously have a significant impact on employee performance. The study concludes that improving discipline, maintaining effective communication, and managing stress levels are essential strategies to enhance employee productivity. Managers should create supportive work environments and develop communication channels that encourage collaboration and stress resilience.